2009
DOI: 10.1128/aac.00588-08
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of High-Dose Oseltamivir in Healthy Volunteers

Abstract: The effects of loading doses and probenecid coadministration on oseltamivir pharmacokinetics at four increasing dose levels in groups of eight healthy adult Thai volunteers (125 individual series) were evaluated. Doses of up to 675 mg were well-tolerated. The pharmacokinetics were dose linear. Oseltamivir phosphate (OS) was rapidly and completely absorbed and converted (median conversion level, 93%) to the active carboxylate metabolite. Median elimination half-lives (and 95% confidence intervals [CI]) were 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 39 publications
4
122
0
1
Order By: Relevance
“…[9][10][11][12][13][14][15] Although there was some delay in the gastrointestinal absorption of the drug after nasogastric or nasojejunal administration (Table 2), the final area under the curve for the carboxylate metabolite at the 75-mg dose in our primary study cohort was also similar to values found in ambulatory patients. 12,13,15 The achieved concentration of oseltamivir in relation to the sensitivity of the influenza virus is associated with the probability of viral eradication and clinical cure in vivo.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15] Although there was some delay in the gastrointestinal absorption of the drug after nasogastric or nasojejunal administration (Table 2), the final area under the curve for the carboxylate metabolite at the 75-mg dose in our primary study cohort was also similar to values found in ambulatory patients. 12,13,15 The achieved concentration of oseltamivir in relation to the sensitivity of the influenza virus is associated with the probability of viral eradication and clinical cure in vivo.…”
Section: Discussionsupporting
confidence: 64%
“…The pharmacokinetic parameters identified were the absorption rate constant from the gastrointestinal tract, the metabolic conversion from oseltamivir free base to its carboxylate metabolite (i.e., assuming complete conversion), the elimination rate constant of the metabolite, and the apparent volume of distribution of oseltamivir free base and of the carboxylate metabolite. To examine renal function as a covariate with pharmacokinetic parameters, we used creatinine clearance as determined Using an approach previously validated by Wattanagoon and colleagues, 9 we performed dose normalization of pharmacokinetic parameters and concentrations to allow for comparative inclusion of patients who received the nonstandard regimen of 150 mg twice daily. We compared parameters of clinical outcomes, such as duration of hospital stay and survival, using actual drug concentration and area-under-thecurve values for whichever regimen the patient was receiving.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…In a previous report by Shi et al (27), several naturally occurring HCE1 polymorphic variants with different in vitro hydrolysis rates from the wild-type enzyme were described, and genetic variation in the HCE1 gene was also reported previously by other groups (3,28). The clinical relevance of these polymorphisms is unclear, and there are currently only sparse clinical data on the effect of genetic esterase polymorphisms on oseltamivir (and OC) pharmacokinetics in humans (30). Nevertheless, a complete blockade of the conversion of oseltamivir to OC could theoretically occur and lead to enhanced oseltamivir concentrations.…”
mentioning
confidence: 88%
“…Oseltamivir phosphate was dissolved in 0.5% methylcellulose solution at 10 mg/ml and administered into the stomach with catheters (30 mg/kg) once a day for 5 days. With this protocol, the maximum concentration of drug in plasma (C max ) and the area under the concentration-time curve (AUC) for oseltamivir carboxylate in macaques were larger than those in adult humans administered oseltamivir phosphate twice a day (75 mg ϫ 2) (25,26). Peramivir hydrate (10 mg/ml, 30 mg/kg) was intravenously injected into macaques once a day for 5 days (27).…”
mentioning
confidence: 99%